The Knowledge Management Practices As Moderator In The Relationship Between Corporate Strategy And Firm Performance Among Public-Listed Organizations In Malaysia - Raja Kasim, Raja Suzana; Che Rose, Raduan; Uli, Jegak; Idris, Khairuddin (2007)
Despite interest in managing knowledge, however, there has been very little research about incorporating the knowledge management practices in the corporate strategy agenda of the organization. Lack of empirical evidence creates a gap between theory and practices of knowledge management in the corporate strategy issues. In this study, the researchers integrate theories on the knowledge-based view and the resources-based view of the firm and strategy to develop a suitable framework and model for knowledge management research; develop a knowledge management construct and empirically tested the research model within the moderation perspective along with the Miles and Snow’s strategy typology. In particular, the influenced of the knowledge management practices as key moderating variable which have been neglected in Malaysian previous studies are examined. The theoretical model is empirically tested using data from 123 public-listed organizations in Malaysia. Data from the survey is analyzed using the higher order interaction effects of the Moderated Multiple Regressions analysis. Results indicate that corporate strategy and the knowledge management practices positively impact firm performance. The moderating effect of the knowledge management practices explains 13% of variance in firm performance increase and beyond the increased explained by the corporate strategy. An important management implication of this study is that it confirms that either the corporate strategy alone or knowledge-related activities alone do not adequately enhance business activities which in turn leads to contribute to the performance of the organizations. Instead, this study suggests that greater utilization of the knowledge management practices in crafting the corporate strategy both in the aspect of operational effectiveness (internally) and strategic positioning (externally) help organizations to pinpoint areas within the organizations where the knowledge management practices is creating value. It is the fit between the organization structure, process and the corporate goals for the knowledge management practices facilitates the success of a good structure, which in turn, leads to better firm performance and contribute the understanding of how the knowledge management practices can improve firm performance.